2021
DOI: 10.1002/bab.2090
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of glutathioneS‐transferase enzyme from brown meagre (Sciaena umbra) and inhibitory effects of heavy metals

Abstract: Glutathione S-transferase (GST) detoxifies a broad spectrum of xenobiotics, especially in chemotherapeutic drugs, endogenous molecules, and environmental pollutants. Since the enzyme metabolizes toxic compounds, it has been extensively studied in many living things including aquatic organisms. In the current study, the GST enzyme was purified from brown meagre (Sciaena umbra) muscle tissue for the first time. Then, kinetic parameters of the enzyme were determined as optimum ionic strength: 20 mM Tris/HCl, opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…GSTs are a family of antioxidant isoenzymes that participate in the cellular detoxification of several xenobiotics. The inhibitory effects of metals in GST activity may be harmful to the cells (Guven and Soydan, 2022). Several studies showed decreased GST activities following HMs exposure in testes of mammals, such as decreased GST after 20mg/kg of Pb (i.p.)…”
Section: Testes Alterationsmentioning
confidence: 99%
“…GSTs are a family of antioxidant isoenzymes that participate in the cellular detoxification of several xenobiotics. The inhibitory effects of metals in GST activity may be harmful to the cells (Guven and Soydan, 2022). Several studies showed decreased GST activities following HMs exposure in testes of mammals, such as decreased GST after 20mg/kg of Pb (i.p.)…”
Section: Testes Alterationsmentioning
confidence: 99%